2013
DOI: 10.1016/j.cub.2012.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Tracks Carbon Dioxide in Flight

Abstract: Carbon dioxide (CO(2)) elicits an attractive host-seeking response from mosquitos yet is innately aversive to Drosophila melanogaster despite being a plentiful byproduct of attractive fermenting food sources. Prior studies used walking flies exclusively, yet adults track distant food sources on the wing. Here we show that a fly tethered within a magnetic field allowing free rotation about the yaw axis actively seeks a narrow CO(2) plume during flight. Genetic disruption of the canonical CO(2)-sensing olfactory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 34 publications
2
51
1
Order By: Relevance
“…S5) (Larsson et al, 2004;Stensmyr et al, 2003), and binary mixtures of these compounds largely follow the rules we derived with our odor set. Alternatively, the difference may arise from the fact that flies are walking in our paradigm, while they are flying in the wind tunnel, a difference that has been suggested to influence the evaluation of CO 2 (Wasserman et al, 2013). A fine-scale analysis of flight behavior in the wind tunnel particularly focusing on instantaneous responses upon plume encounter will be needed to resolve the reason for the differences between our results and the results provided by Becher and co-workers.…”
Section: The Valence Of Odor Mixturescontrasting
confidence: 44%
“…S5) (Larsson et al, 2004;Stensmyr et al, 2003), and binary mixtures of these compounds largely follow the rules we derived with our odor set. Alternatively, the difference may arise from the fact that flies are walking in our paradigm, while they are flying in the wind tunnel, a difference that has been suggested to influence the evaluation of CO 2 (Wasserman et al, 2013). A fine-scale analysis of flight behavior in the wind tunnel particularly focusing on instantaneous responses upon plume encounter will be needed to resolve the reason for the differences between our results and the results provided by Becher and co-workers.…”
Section: The Valence Of Odor Mixturescontrasting
confidence: 44%
“…In Drosophila, the ionotropic receptors (IRs) IR64a and IR8a work together to detect a drop in sensory lymph pH, which could be induced by a high concentration of CO2 in the environment (Ai et al 2013). A recent study further showed that genetic disruption of the IR64a in Drosophila can alter their in-flight attraction to CO2 (Wasserman et al 2013). Therefore, IRs may be alternative receptors for CO2 detection in species that lack orthologous CO2 GRs (Ai et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that CO 2 elicits behavioral reactions ranging from aversion [5,6] to attraction [12,13] to responses in between [14]. The spectrum of value assignments mirrors the ecological roles that CO 2 is known to play in the daily life of the fly, ranging from indicating the presence of an attractive food source on the wing [15] to signaling danger as a co-indicator of fly stress pheromone [5,16].…”
Section: Current Biologymentioning
confidence: 91%